Analisis Pengujian terhadap Model Aplikasi Sistem Pakar Diagnosis Penyakit Paru-Paru Berbasis Web - Mohamad Aghust Kurniawan; Galih Ariprawira; Andri Sahata Sitanggang (Faletehan Health Journal, 2021)
Data from the Indonesian Cancer Information & Support Center (CISC) shows lung cancer is the leading cause of cancer death with a total of 14 percent. The mortality rate in Indonesia reaches 88 percent. The possible treatment is to conduct an early examination through an Expert System. The research purpose was to design an Expert System of web-based lung disease diagnosis that can help people consult their lung disease without having to come straight to hospital, public health center, or doctor. In making the application model, the Expert System applied a descriptive method and action. Meanwhile, in designing the Expert System, the methods used were object-oriented approach method and prototype development method. The results of this study consisted of several stages, namely (1) Analysis into the application model/design/prototype, (2) Model/Prototype testing, and (3) Improvement of Expert System Model/Design/Prototype. The researchers expected that the Expert System will help people get direct information services about lung diseases and the diagnosis and help doctors do the treatment supervision to the patients.